SELF-DISCLOSURE CONTRIBUTION ON EARLY-ADULT MALE MARITAL SATISFACTION - Quroyzhin Kartika Rini; Retnaningsih Retnaningsih (Universitas Gunadarma, 2007)
Marriage and family life is very important for human being because from them, he/she will shape his/her own life, and from the family he/she learns to interact with surroundings. Each person wants to have a one-ina-lifetime-happines-marriage. One of the criteria that affect marriage is the marital satisfaction. Thus, self-disclosure is mentioned as one thing that affecting marital communication to make a real marital satisfaction. In daily life, women has better self-disclosure than men to articulate the feelings verbally. This facts is important to be known because men is more honest and open about himself in make a marital communication to have more marital satisfaction with his wife. The aim of this study is to know the contribution of self-disclosure to marital satisfaction in men. The results shows that self-disclosure has contribution around 56,9%, and the rest are another factors such as the equalitarian, sex, social life, region, and income. Beside that, the participants of this study has high score in marital satisfaction, and moderate score in self-disclosure.Key words: marital satisfaction, self-disclosure, men